Effects of hydroethanolic and sequential extraction on the toxic potential of extracts from different parts of Parkia platycephala from the Cerrado of Tocantins (Research, Society and Development, 2022)
Commonly, the use of plants as herbal medicines is perceived, however, the fine line between treatment and intoxication is a reality. This study evaluated the toxicity of extracts from the leaf, bark, flower and seed of Parkia platycephala through root growth of Allium cepa. Two extraction methodologies were carried out, one polar and one sequential, both using Soxhlet apparatus, obtaining crude extracts (FEB, CEB, FREB, SEB), methanolic (FEM, CEB, FREM, SEM) and ethanolic (FEE, CEE, FREE, SEE) of leaf, bark, flower and seed, respectively. The toxic potential of each extract was evaluated at three concentrations (50, 250, 750 µg/ml), with mineral water as a negative control. It was observed that of the 36 samples analyzed, 25% stimulated the root growth of A. cepa under the conditions evaluated and 39% maintained the growth characteristics of the negative control, indicating non-toxicity of these extracts. The best rates of root growth were obtained in the bark (2.7) and flower (2.0) by the sequential methodology. The crude bark extract (CEB) did not show toxicity at the concentrations evaluated. Seed extracts from sequential extraction showed toxicity from the concentration of 250 µg/ml. At a concentration of 750 µg/ml, only one extract showed no toxicity. In view of the results presented, it is believed in the potential therapeutic use of the species P. platycephala at concentrations below 250 µg/ml, however more detailed studies are needed to confirm the toxicity of the extracts of the species.